Dynamics of Biological Macromolecules: Not a Simple Slaving by Hydration Water - Khodadadi, S. (The Biophysical Society, 2010)
We studied the dynamics of hydrated tRNA using neutron and dielectric spectroscopy techniques. A comparison of our results with earlier data reveals that the dynamics of hydrated tRNA is slower and varies more strongly with temperature than the dynamics of hydrated proteins. At the same time, tRNA appears to have faster dynamics than DNA. We demonstrate that a similar difference appears in the dynamics of hydration water for these biomolecules. The results and analysis contradict the traditional view of slaved dynamics, which assumes that the dynamics of biological macromolecules just follows the dynamics of hydration water. Our results demonstrate that the dynamics of biological macromolecules and their hydration water depends strongly on the chemical and three-dimensional structures of the biomolecules. We conclude that the whole concept of slaving dynamics should be reconsidered, and that the mutual influence of biomolecules and their hydration water must be taken into account.